Assessment the role of some Bacillus strains in improvement rex rabbits resistance against ETEC challenge. (April 2022) - Wang, Jie; Wen, Bin; Zeng, Yan; Wang, Hesong; Zhao, Wei; Zhou, Yi; Liu, Lei; Wang, Ping; Pan, Kangcheng; Jing, Bo; Ni, Xueqin; Zeng, Dong
Abstract: Increasing reports have indicated that specific strains of probiotic Bacillus have the potential to prevent diseases. The purpose of this study was to explore the effects of three Bacillus strains ( Bacillus subtilis BSWJ2017001, Bacillus pumilus BSWJ2017002, and B. subtilis BSWJ2017003) mixture dietary supplementation on rex rabbits infected with enterotoxigenic Escherichia coli (ETEC). In this study, 60 35-day-old weaning rex rabbits were separated into two groups randomly: control group (fed basal diet with no antibiotics) and Bacillus strains group (fed basal diet containing 1.0 × 10 6 CFU/g Bacillus strains mixture). After 8 weeks of feeding, the rex rabbits were inoculated orally with 5.0 mL of ETEC (1.0 × 10 9 CFU/mL) and assessed at 0, 12, and 24 h. The Bacillus strains mixture attenuated the oxidative damage, diarrhea severity, and intestinal damage of ETEC infected rabbits. It also significantly increased the population of Lactobacillus spp., and Bifidobacterium spp., and decreased the population of Enterococcus spp.. Moreover, Bacillus strains group exhibited higher levels of toll-like receptor (TLR) 2, anti-inflammatory cytokines, secretory immunoglobulin A, and intestinal barrier-related genes than control group, as well as lower levels of TLR-4 and pro-inflammatory cytokines. These results demonstrated that Bacillus strains mixture could attenuate injury caused by ETEC and enhance disease resistance by improving specific intestinal microbiota members and immunity in weaning rex rabbits . Highlights: Bacillu s strains could attenuate injury caused by ETEC in rex rabbits. Bacillus strains could enhance disease resistance by improving intestinal microbiota. Bacillus strains could enhance disease resistance by improving immunity.